Analysis of The Acceptance Level Of Digital Wallet Users in Digitally Parking Payment Using The Technology Acceptance Model Approach - Launtu, Ansir; Nurlina; Mentalita, Hotma; Ilyas, Arifai; Munizu, Musran (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to identify the factors that affect users' acceptability of using an e-wallet to pay for parking. We used a cross-sectional quantitative approach to carry out this study. We distributed questionnaires and conducted surveys to gather data. This study's population includes anybody who pays with a mobile wallet and utilizes parking services. One hundred people made up the study's sample. Using SmartPLS, we performed statistical data analysis that involved hypothesis testing, inner and outer model analysis, and examination of the data. It's evident from the hypothesis results that using e-wallets to pay for parking makes consumers feel more productive. Users' perception of the usefulness of utilizing e-wallets to pay for parking is indicated by their approval of the PU3 indication. However, because security rejects their goal of using e-wallets, users do not feel secure when using them. Perceived utility and subjective norms are the main determinants of e-wallet acceptance as a payment method; design comes in second. The hypothesis that most influences this research is the relationship between perceived ease of use and perceived usefulness, with perceived ease of use being influenced by design.